A community for students.
Here's the question you clicked on:
← 55 members online
 0 viewing
anonymous
 5 years ago
Guys, a simple question please
How can I turn " M=e^t  e^tM "
into
" M= e^t / (1 + e^t) "
anonymous
 5 years ago
Guys, a simple question please How can I turn " M=e^t  e^tM " into " M= e^t / (1 + e^t) "

This Question is Closed

amistre64
 5 years ago
Best ResponseYou've already chosen the best response.0equate them and see what you can do to them :) maybe

anonymous
 5 years ago
Best ResponseYou've already chosen the best response.0m+e^tm=e^t m(1+e^t)=e^t m=e^t/(1+e^t)

amistre64
 5 years ago
Best ResponseYou've already chosen the best response.0e^t e^(tM) = e^t/(1+e^t) ; *(1+e^t) both sides (e^t e^(tM))(1+e^t) = e^t

amistre64
 5 years ago
Best ResponseYou've already chosen the best response.0e^t +e^2t  e^(tM)  e^(t^2M) = e^t

anonymous
 5 years ago
Best ResponseYou've already chosen the best response.0Oh, right, I've got it! Thank you very much ! :D
Ask your own question
Sign UpFind more explanations on OpenStudy
Your question is ready. Sign up for free to start getting answers.
spraguer
(Moderator)
5
→ View Detailed Profile
is replying to Can someone tell me what button the professor is hitting...
23
 Teamwork 19 Teammate
 Problem Solving 19 Hero
 Engagement 19 Mad Hatter
 You have blocked this person.
 ✔ You're a fan Checking fan status...
Thanks for being so helpful in mathematics. If you are getting quality help, make sure you spread the word about OpenStudy.